Nếu \({\log _a}x = {1 \over 2}{\log _a}9 - {\log _a}5 + {\log _a}2\,\,\,\,(a > 0,\,a \ne 1)\) thì x bằng:

Câu hỏi :

Nếu \({\log _a}x = {1 \over 2}{\log _a}9 - {\log _a}5 + {\log _a}2\,\,\,\,(a > 0,\,a \ne 1)\) thì x bằng:

A. \({2 \over 5}\)    

B. \({3 \over 5}\)  

C. \({6 \over 5}\)    

D. \(3\)  

* Đáp án

C

* Hướng dẫn giải

Ta có: \({\log _a}x = \dfrac{1}{2}{\log _a}9 - {\log _a}5 + {\log _a}2\, \)\(= {\log _a}3 - {\log _a}5 + {\log _a}2\)

\( \Leftrightarrow {\log _a}x = {\log _a}6 - {\log _a}5 = {\log _a}\dfrac{6}{5} \)

\(\Leftrightarrow x = \dfrac{6}{5}.\)

Chọn đáp án C.

Copyright © 2021 HOCTAP247